Physiological response of goldsinny wrasse to global climate change - Hammar Perry, Diana (Swedish University of Agricultural Sciences, 2024)
In order to understand the physiological effects of global climate change on goldsinny wrasse, a multi-stressor experiment was conducted exposing the fish to four weeks of experimental conditions with treatments consisting of control conditions (salinity approx 28, temp 13°C, pH approx 8.1), low salinity (17), high temperature (19°C), low ph (7.5) and the combination of all three stressors combined (multi-stressor treatment salinity 17, temp 19°C, and pH 7.5).
Potential physiological stress was evaluated by measuring growth (weight and length), oxygen consumption using respirometry, and liver oxidative stress analyses (ratio GSSG-GSH, GSSG, GSH, CAT, GST, GR and LPO).

Data from the Weight Length file contains information related to experimental treatment conditions, fish ID, and weight (g) and length (cm) at the end of the exposure period (4 columns, 123 rows).

Data from the ratio GSSG-GSH, GSSG, GSH, CAT, GST, GR and LPO files are from enzymatic measurements of liver samples for oxidative stress analyses and include treatment and fish ID for each biomarker.

The ratio GSSG-GSH file - 3 columns, 80 rows; the GSSG file – 3 columns, 80 rows; the GSH file – 3 columns, 80 rows; the CAT file - 3 columns, 74 rows; the GST file – 3 columns, 77 rows; the GR file – 3 columns, 75 rows; the LPO file – 3 columns, 77 rows. Glutathione-reductase = GR (nmol/mg protein/min), Glutathione-S-transferase = GST (µmol/mg protein/min), Catalase = CAT (µmol/mg protein/min), Reduced glutathione = GSH (µmol/mg liver), Oxidized glutathione = GSSG (µmol/mg liver), Ratio oxidized/reduced = %GSSG/GSH (%), Lipid peroxidation = LPO (nmol MDA/ml).

Data from the Rest, max and scope respirometry file contains oxygen consumption data MO2 which stands for mass specific O2 uptake and SMR for standard metabolic rate. SMR, maximum MO2 and aerobic scope (mg O2 h-1). It also includes treatment, fish ID, and weight (g) – 6 columns, 76 rows.

Ett multi-stressorexperiment genomfördes för att bedöma det fysiologiska respons av stensnultra på globala klimatförändringsstressorer. En mer detaljerad beskrivning kan ses på engelska.
Fysiologisk respons hos stensnultra på globala klimatförändringar
Keywords: HEAT WAVE; ocean acidification; physiology; fysiologi; Ctenolabrus rupestris; stensnultra; ctenolabrus rupestris (linnaeus, 1758); ocean acidification; havsförsurning; marine heat wave; värmeböljor; marine; marin; freshening; utsötade hav; goldsinny wrasse; stensnultra; Climate change; Klimatförändring; multi-stressor experiment; multi-stressor experiment; Climate Science; Klimatvetenskap; Ecology; Ekologi; Other Biological Topics; Annan biologi; Other Natural Sciences; Annan naturvetenskap